1984
DOI: 10.1051/rphysap:01984001904033300
|View full text |Cite
|
Sign up to set email alerts
|

Passivation par l'hydrogène de défauts recombinants dans les photopiles réalisées sur rubans de silicium polycristallin RAD

Abstract: Cet article présente les résultats d'une étude exploratoire de la passivation par l'hydrogène des défauts recombinants dans les rubans de silicium polycristallin élaborés par la méthode RAD. L'incorporation d'hydrogène a été effectuée sur des photopiles nues au moyen d'une source d'ions du type Kaufman. On montre que les caractéristiques globales des photopiles — photocourant, tension de circuit ouvert et facteur de forme — sont considérablement améliorées tandis que leurs distributions sont resserrées. Ces am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1985
1985
1989
1989

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Hydrogen can be introduced into silicon by several means : bombardment in a Kaufman source [14,15], plasma annealing [16], electrolyte charging [12]. Plasma annealing and electrolyte charging have been investigated in the present study, in order to quantify the diffusion mechanisms of hydrogen.…”
mentioning
confidence: 99%
“…Hydrogen can be introduced into silicon by several means : bombardment in a Kaufman source [14,15], plasma annealing [16], electrolyte charging [12]. Plasma annealing and electrolyte charging have been investigated in the present study, in order to quantify the diffusion mechanisms of hydrogen.…”
mentioning
confidence: 99%
“…For example, it has been demonstrated that implantation of molecular or atomic hydrogen improves the electrical properties such as the diffusion length in both ingots and ribbons [1][2][3][4][5]. Diffusion at low temperature of selected impurities such as Cu and Al into polycrystalline Si was also found to improve the minority carrier diffusion length [6].…”
mentioning
confidence: 99%